The incas and their predecersors - Lowie, Robert (1961)
Ancient civilization in the Andes was centered in what is now the Republic of Peru. The great mountain mass of the Andes, which runs down the entire west coast of South America, divides Peru into three strikingly different life zones. The mountains of the interior are high and rugged, with fertile river basins isolated Iroin each other by spectacular peaks and connected only by high, difficult passes. To the west, the narrow coastal plain is one of the world s driest deserts. I hough it receives no rain except for an occasional thick mist, this desert is made habitable by numerous little rivers which bring water down from the mountains, permitting intensive irrigation agriculture in their narrow valleys. Furthermore, thanks to the cold Peru (Humboldt) Current, the I ac ific Ocean off the Peruvian coast teems with fish and other sea food. The third life zone is on the eastern slopes of the mountains, where equatorial heat and excessive rainfall combine to produce a lush tropical forest. The mighty rivers of the Amazon system flow down these slopes onto the tropical flat land which makes up the heart of South America.